In Vitro Antioxidant Activity and Anticonvulsant Properties on Zebrafish PTZ-Induced Seizure Model of a Tilia viridis Aqueous Extract - Elina Malén Saint Martin; Ayelen Morena Sosa; Carolina Soledad Martinez; Jimena Prieto; Carla Marrassini; Cecilia Beatriz Dobrecky; María Rosario Alonso; Claudia Anesini (Korean Pharmacopuncture Institute, 2024)
Objectives: Tilia viridis (Bayer) Simonk. (Malvaceae) is widely distributed in Argentina and employed for its tranquilizing properties. Other species of the genus (Tilia europaea L., Tilia cordata Mill., Tilia platyphyllos Scop.) have been traditionally used for the treatment of epilepsy. Epilepsy affects approximately 65 million people worldwide and is characterized by an imbalance between excitatory and inhibitory processes in the brain, leading to unpredictable, unprovoked, recurrent seizures. Current pharmacological interventions often present mild to moderately severe side effects. Epilepsy has been associated with oxidative and nitrative stress as well as neuroinflammation. Herbal medicine therapies may offer new treatment options with multi-target antioxidant and anticonvulsant effects for patients whose seizures remain uncontrolled, potentially providing cost-effective solutions for individuals worldwide suffering from uncontrolled epilepsy.The aim of this study was to demonstrate the anticonvulsant activity of a standardized T. viridis aqueous extract (TE).Methods: Study of the constituents of TE, TE's antioxidant and anticonvulsant activities and toxicity, and analysis of the possible relation between the potential activities and the compounds present in the extract. In order to demonstrate TE's anticonvulsant activity a zebrafish model was used. The study also assessed TE's toxicity and antioxidant activity. To standardize the extract, total polyphenols and flavonoids were quantified and specific flavonoids were identified and quantified using HPLC-MS/MS and HPLC-UV.Results: TE exhibited anticonvulsant activity at low concentrations and demonstrated antioxidant effects by scavenging free radicals, exhibiting superoxide dismutase and peroxidase- like activities, as well as inhibiting lipoperoxidation. These actions can be attributed to the presence of polyphenols, particularly flavonoids.Conclusion: TE holds promise as a complementary herbal medicine in the treatment of epilepsy and may also offer benefits for other neuropathies associated with oxidative stress, such as Parkinson's disease and Alzheimer's disease.